The association of body mass index with safety and effectiveness of first-line carboplatin-based chemotherapy in patients with metastatic non-small cell lung cancer. (2023) - Kicken, M.P.; Kilinc, H.D.; Cramer-van der Welle, C.M.; Houterman, S.; van den Borne, B.E.E.M.; Smit, A.A.J.; van de Garde, E.M.W.; Deenen, M.J.; ,
Highlights: Progression free survival is higher in overweight patients treated with carboplatin. Overall survival higher in overweight patients treated with carboplatin. Survival is comparable for obese patients and normal weight patients. Obesity increases the risk of carboplatin-induced severe thrombocytopenia. Abstract: Introduction: Carboplatin is an anticancer drug used for treatment of various types of cancer including non-small cell lung cancer (NSCLC). Dosing is based on estimated glomerular filtration rate (GFR) using the Cockcroft-Gault formula. In overweight patients, the GFR is more likely overestimated, resulting in a potentially overdose of carboplatin affecting treatment response. This study investigated the association of body mass index (BMI) on overall survival (OS) and progression-free survival (PFS) in stage-IV NSCLC patients treated with first-line carboplatin-based chemotherapy. Secondary safety endpoints were thrombocytopenia and toxicity-related hospitalizations. Materials and methods: This was a retrospective multicenter cohort study. Patients were categorized according to BMI<25.0 kg/m 2 (normal weight and reference), 25.0-29.9 kg/m 2 (overweight) or ≥30.0 kg/m 2 (obese). For survival analyses adjusted hazard ratios [aHR] were calculated using multivariate Cox regression analysis. Secondary outcomes were analyzed using multivariate logistic regression providing adjusted odd ratios [aOR]. Results: Overweight patients (n=174) had a significantly better OS (aHR=0.72, 95%-CI:0.59-0.89) and PFS (aHR=0.74, 95%-CI:0.61-0.90) compared to normal weight patients (n=268). OS nor PFS were different in obese (n=51) compared to normal weight patients. However, obesity was associated with significantly higher incidences of thrombocytopenia grade ≥3 (aOR=3.47, 95%-CI:1.75-6.90). Conclusion: This study shows a significantly longer survival for overweight compared to normal weight patients. Obese patients have an increased risk for grade ≥3 thrombocytopenia without a difference in survival following carboplatin-based chemotherapy. The implications for clinical practice are to use the Cockcroft-Gault formula with caution in patients with BMI≥30.0 kg/m 2, and to verify calculated dosing of carboplatin for appropriateness.